History of the Codification of Hadith and Its Development into the Era of Digitalization - Maulana Hasan Hasibuan; Rahmi Syahriza; Asrar Mabrur Faza (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
The orientation of this article is to discuss the meaning of hadith and its development. The tradition of writing hadith has occurred since the time of the Prophet. The companions received the hadith from the Prophet's assembly and then recorded what the Prophet had said. However, the number of friends who can write is still very small, so the recorded hadith material is limited. Apart from that, the attention of the companions is still based on maintaining the Koran, making hadith records only spread to the companions' sahifah. The way of narrators in obtaining and conveying hadith is different between the time of the Prophet and the time of Khulafa’ al-Rasyidin. Likewise, the narration of hadith during the time of friends is not the same as the narration of hadith in the period after. Hadith narration during the time of the Prophet was more free because there were no conditions that had to be met. Because during the time of the Prophet there was no definite evidence that there had been falsification of hadiths, and it was also easier for the Prophet to carry out examinations if there was a hadith whose validity was doubtful. During the time of Khulafa’ al-Rasyidin there was a simplification of hadith narration, where narrators who wanted to narrate hadith had to take an oath or present witnesses if the hadith written was true from the Prophet. It was only when Caliph Umar ibn Abdul Aziz became caliph that hadith began to undergo codification, and developed in the current modern century, digitalization of the realm of hadith of the Prophet SAW.